STUDY OF THE ROLE OF ETHANOL ALCOHOL EXTRACT OF Laurus nobilis LEAVES IN THE EFFICIENCY OF THE MALE REPRODUCTIVE SYSTEM IN ALBINO RATS EXPOSED TO OXIDATIVE STRESS - JABER, ZAHRAA HUSAM; MAHDI, ZAINAB SHNEWER (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Aims: This study was conducted on adult males of albino rat to reveal the protective role of ethanol alcohol extract of leaves of laurel plant Laurus nobilis on the efficiency of the male reproductive system. Study Design: 24 rats were used in the experiment, but divided into (4 groups) for treatments, at a rate of 6 rats for each treatment, at the age of 12 weeks. Place and Duration of Study: The animals were brought from sources outside the university, and were transferred to the place of study in the animal house of the College of Education for Girls / University of Kufa. Methodology: The first treatment was the negative control treatment, where the animals were given only water and ration daily for 60 days. The second treatment was considered a positive control. It was dosed orally with hydrogen peroxide (1 mL / 200 g of body weight per day for 60 days, and the third treatment dosed the alcoholic extract of bay leaves). Laurus nobilis (300 mg/kg) daily for 60 days, while the fourth treatment was dosed with alcoholic extract of bay leaves and hydrogen peroxide daily for 60 days. The dose selected. Based on weight or rats and age. Rats were weighed before and after conducting the experiment, then the animals were sacrificed by the (euthanasia and blood samples) were collected for the purpose of conducting the experiment. Biochemical examinations. The genitals (testes and epididymis) and some glands (such as the seminal vesicle and prostate) were removed and then weighed. Results: There was a significant (P < 0.05) decrease in body weight in the group treated with alcoholic extract of Laurus nobilis leaves at a concentration of 300 mg/kg for 60 days, while there was a significant (P < 0.05) increase in body weight in the positive control group compared with the negative control group. There was a significant decrease (P < 0.05) in the mean weights of the genitals and accessory glands in the positive control group compared to the negative control group. On the other hand, there was a significant increase (P < 0.05) in the mean weights of organs and accessory glands in all groups compared with the positive control group, in addition to the presence of significant differences between the treatments. The results of the current study indicated that there was a significant decrease (P < 0.05) in the number of sperms in the testes and epididymis, the percentage of motile and progressively moving sperms in the tail of the epididymis and the percentage of viable sperms in the tail of the epididymis in the positive control group compared with the negative control group. On the other hand, the ficant increase (P < 0.05) in the averages of these parameters in all groups treated with alcoholic extract of bay leaves and hydrogen peroxide compared with the positive control group, in addition to the presence of significant differences between the treatments. While the results showed a significant increase (P < 0.05) in the average percentage of symmetrical sperms in the tail of the epididymis of the animals of the positive control group compared to the animals of the negative control group, while the treatment with alcoholic extract of bay leaves caused a significant decrease (P < 0.05) in the mean Asymmetric sperm percentage in the rest of the groups compared with the positive control group, in addition to noting that there are significant differences between the treatments. It was also found that there was a significant decrease (P < 0.05) in the levels of testosterone, luteinizing hormone (LH) and follicle stimulating hormone (FSH) in the animals of the positive control group compared to the animals of the negative control group. In the average levels of these hormones in all groups compared with the positive control group. Conclusion: Through the results, we conclude that the alcoholic extract of bay leaves, which has an antioxidant property, can prevent the harmful effects and oxidative stress caused by hydrogen peroxide.